Infection of abdominal surgical wounds: Assessment of advanced healing results in the hospitalization area (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The development of surgical wound infection is related to the degree of bacterial contamination before and during surgery, the virulence of the infecting organism, and the host's defenses. It is the most frequent cause of nosocomial infections among hospitalized patients and represents 40% of the causes of nosocomial infection in surgical patients.Objectives proposed were: Define the prevalence of the most frequent microorganisms in abdominal surgical wound infection, identify the influence of hospital stay with the risk of presenting abdominal surgical wound infection. Know the prevalence of abdominal surgical wound infection according to age ranges and determine the prevalence of abdominal surgical wound infection according to gender.It was a descriptive, retrospective, non-experimental cross-sectional investigation. It corresponded to an investigation carried out during the period January-December 2019 at Abel Gilbert Pontón Specialty Hospital, Guayaquil, Ecuador, a total of [n = 157 (100%)] samples were taken that met the criteria to be included in this study , of which (83.4%) were colonized by Gram negative bacteria and (16.6%) by Gram positive bacteria, leading the microbiological profile Escherichia coli [n = 55 (35%)] with a prevalence of 25% , patients that stay in the hospital within the first 34 days presented a greater probability of abdominal surgical wound infection and in relation to the age range and gender, the age group of 41 to 63 years had a prevalence of 41.2%, and the female gender of 37%.
Keywords: Infections; abdominal surgical wounds; hospitalization